2017
DOI: 10.1111/1749-4877.12245
|View full text |Cite
|
Sign up to set email alerts
|

Like or dislike: Response of rodents to the odor of plant secondary metabolites

Abstract: Rodents, including common voles (Microtus arvalis) and house mice (Mus musculus) cause immense pre‐harvest and post‐harvest losses. Therefore, developing methods that mitigate these losses while maintaining their role in ecosystems is a priority. Several plant secondary metabolites (PSM) which significantly reduce food intake of both species under laboratory conditions have been identified. However, before these can be used in rodent pest management, they must be tested under more natural conditions where othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
(55 reference statements)
0
12
1
Order By: Relevance
“…In our study, for these three dominant plant species, there exist huge differences in secondary compounds, digestible nutrients and fibre. Properties of plant quality could affect the feeding behaviour and modulate the gut microbiota of voles, which influenced the growth and health of voles (Hansen, Stolter, Imholt, & Jacob, ). For example, silica in plant leaves has a detrimental effect on voles by wearing tooth, inducing intestinal abrasion and reducing plant palatability and digestibility (Wieczorek, Zub, Szafranska, Ksiazek, & Konarzewski, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, for these three dominant plant species, there exist huge differences in secondary compounds, digestible nutrients and fibre. Properties of plant quality could affect the feeding behaviour and modulate the gut microbiota of voles, which influenced the growth and health of voles (Hansen, Stolter, Imholt, & Jacob, ). For example, silica in plant leaves has a detrimental effect on voles by wearing tooth, inducing intestinal abrasion and reducing plant palatability and digestibility (Wieczorek, Zub, Szafranska, Ksiazek, & Konarzewski, ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, for these three dominant plant species, there exist huge differences in secondary compounds, digestible nutrients and fibre. Properties of plant quality could affect the feeding behaviour and modulate the gut microbiota of voles, which influenced the growth and health of voles (Hansen, Stolter, Imholt, & Jacob, 2017 , 2017). Evidence indicated that the gut microbiota can also be affected by the fructose-to-glucose ratios of diets (Noble et al, 2017) and dietary tannins (Kohl et al, 2016) in diets.…”
Section: Discussionsmentioning
confidence: 99%
“…They also found that rats preferred foods with high carbohydrate content and that rats were less neophobic to foods with high sugar content. In Germany, Hansen et al (2016Hansen et al ( , 2017 found that some rodents (house mice (Mus musculus) and voles (Microtis arvalis)) were attracted to some plant secondary metabolites, whereas other plant secondary metabolites had a repellent effect. In the United Kingdom, Inglis et al (1996) found wide variation in Norway rat responses to new foods, but also to new food containers.…”
Section: Discussionmentioning
confidence: 99%
“…When the vector beetle feeds on pine trees, the volatile concentrations from the pine increase rapidly (Su et al ., 2008; Niu et al ., 2012; Zhao et al ., 2014; Chen et al ., 2018). The accumulation of volatiles in response to herbivore or pathogen attack is an important component of host defence (Lewinsohn et al ., 1991; Keeling and Bohlmann, 2006; Hansen et al ., 2017). However, B. xylophilus might take advantage of these volatile accumulations for its survival (Figs 4 and 5).…”
Section: Discussionmentioning
confidence: 99%